Found a cure - Ultra Nate; Strictly Rhythm Records (United States : Strictly Rhythm Records, 1998)
Contains four tracks featured in the album Situation : Critical.
CD 1 : Found A Cure (Full Intention Club Mix) -- Free (Album version) -- Found A Cure (Album version) -- Free (Full Intention Club Mix).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English